ANALISIS KETERAMPILAN MENULIS PERMULAAN MENGGUNAKAN MEDIA GAMBAR PADA SISWA KELAS 1 SDN TELAGA BIRU 1 BANJARMASIN - Henriani; Arifin, Johan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the early writing skills of first-grade students and analyze the use of picture media in improving these skills at SDN Telaga Biru 1 Banjarmasin. This research employed a qualitative approach with a descriptive method. The subjects consisted of one first-grade homeroom teacher and 25 first-grade students. Data were collected through semi-structured interviews, classroom observations, and documentation, then analyzed qualitatively and thematically. The results showed that students' early writing skills were in the developing stage and highly heterogeneous. Students still faced motor and cognitive challenges, such as inconsistent letter sizes, irregular shapes, and reversed letter writing. The implementation of modified picture media in the form of tracing lines provided a significant positive impact as visual scaffolding. This media effectively reduced students' cognitive load, enhanced muscle memory through multisensory integration, and significantly boosted students' learning motivation, focus, and self-confidence. In conclusion, picture media is a highly effective tool for bridging abstract language symbols into concrete objects for lower-grade elementary school students.